Unaddressed issues in Janani Suraksha Yojana in India (Nepal Journal of Epidemiology, 2014)
Janani Suraksha Yojana (JSY), a combination scheme of performance based financing and conditional cash transfer for safe motherhood, has increased ante natal coverage and institutional deliveries in India. Although the two concepts have been criticized world over for both positive and negative aspects; rarely the role of these two mechanisms behind the success of JSY has been addressed. Quality, cost-effectiveness and other issues were never given due emphasis under this scheme neither efforts have been made to overcome known drawbacks of these strategies. Considering future of the scheme and sustainability, it is required to evaluate the concepts separately.DOI: http://dx.doi.org/10.3126/nje.v4i1.10137 Nepal Journal of Epidemiology 2014;4 (1): 341-343